Improvement to Work Productivity Among Employees at Tigo Baleh Community Public Health Center Bukittinggi - Winas, Loly Novita; Onasis, Aidil; Aprilliani, Cici; Yasril, Abdi Iswahyudi; Kulsyum, Putri (Jurnal Kesmas Jambi, 2026)
Work productivity is an employee's ability to produce outcomes within an organization. Many factors can affect work productivity, including work stress experienced by employees due to excessive workloads, the working environment among colleagues and superiors, and the motivation of employees and management in their work. These factors can affect employee productivity in achieving set targets. This study aims to identify factors related to work productivity among employees Tigo Baleh Community Health Center, Bukittinggi in 2024. This research utilizes a descriptive-analytic method with a cross-sectional study design. The population comprises 46 employees, with total sampling employed as the sampling method. Data were collected using questionnaires and include both primary and secondary sources. Data analysis was conducted using the chi-square test. The results show that 22 respondents (52.4%) do not experience work-related stress, 24 respondents (57.1%) have positive work motivation, 22 respondents (52.4%) perceive a positive work climate, 31 respondents (73.8%) report good management, and 26 respondents (61.9%) are productive at work. Chi-square test results indicate a significant relationship between work stress and productivity (p=0.014; OR=6.75) and between work motivation and productivity (p=0.003; OR=10). There is no significant relationship between work climate (p=0.231) or management (p=0.720) and productivity. The study concludes that work stress and motivation are significantly related to work productivity. It is recommended that the health center implement effective stress management and provide motivation for employees.